Metagenomics reveals the diversity and role of surface-water microbes in biogeochemical cycles in lakes at different terrain ladders - Zhao, Aiwen; Lu, Yuntao; Li, Qi; Li, Tao; Zhao, Jindong (Frontiers in Environmental Science, 2023)
As the most important component of ecosystems, microbial communities play a significant role in global biogeochemical cycles. Geographical barriers created by topographic differences are proposed as one of the main factors to shape microbial diversity, functional composition and their evolution across aquatic ecosystem. There are few studies that compare the microbial community structure and functional potential of lakes with different terrain ladders (terrains of contrasting elevation levels), especially those involving Qinghai-Tibet Plateau. This study compared microbial 16S rRNA data from 51 lakes with different terrain ladders, showing that the composition of the dominant microbial community was similar, but the microbial abundance was quite different in different terrain ladders. Actinobacteria, Proteobacteria, Cyanobacteria, Planctomycete, Verrucomicrobia and Bacteroidetes were the dominant taxa. Through the correlation analysis between environmental factors and the microbial community structure, it was found that two environmental factors (elevation and salinity) had significant contributions to the microbial composition. Metagenomics of six representative lakes revealed the relationship between microbial composition and metabolic processes related to carbon, nitrogen and sulfur cycles. The comparative analysis of genes related to metabolism cycles showed that functional processes such as aerobic respiration, nitrogen assimilation, the mineralization of nitrogen and sulfur had highest metabolic potential in the ecosystems. The analysis of indicator species based on the metabolic process in the carbon, nitrogen and sulfur cycles showed that the microbial community structure is related to the dominant metabolic functions within biogeochemical cycles. Different dominant species play an important and distinct role in lakes with different gradients. Actinobacteria, Cyanobacteria and Proteobacteria were the most important indicator species on the Qinghai-Tibet Plateau, Yunnan-Guizhou Plateau and the middle and lower reaches of the Yangtze River Plain, respectively. In general, this study explored the functional distribution patterns of the dominant microbial communities in the lakes in biogeocycles.